KOMPETENSI SOSIAL KEPALA MADRASAH DALAM MENINGKATKAN KOMUNIKASI INTERPERSONAL GURU DI MADRASAH ALIYAH SWASTA MADINATUL ‘ULUM PAMENANG MERANGIN JAMBI - Angraini, Rini; Musa; Susanti, Try (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted based on the problem that interpersonal communication between the head of the madrasah and teachers at Madrasah Aliyah Swasta Madinatul ‘Ulum Pamenang, Merangin Jambi had not been implemented optimally. Initial observations indicated that communication tended to be one-way, the intensity of interaction was limited, and teachers were often reluctant to express opinions, which affected the effectiveness of professional relationships and work motivation. The purpose of this research was to describe the forms of social competence possessed by the head of the madrasah in improving teachers’ interpersonal communication, to analyze its implementation, and to identify supporting and inhibiting factors. This research employed a qualitative field research approach conducted at Madrasah Aliyah Swasta Madinatul ‘Ulum Pamenang. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The results showed that the social competence of the head of the madrasah played an important role in improving teachers’ interpersonal communication, particularly through coordination, supervision, guidance, and professional interaction. However, several obstacles were found, including limited communication intensity, lack of structured communication strategies, and psychological distance between the head of the madrasah and teachers. Efforts to overcome these obstacles were carried out through strengthening communication approaches, encouraging participatory interaction, and improving the quality of professional relationships within the madrasah environment.